Design formulation of ostrich feed from palm kernelcake (PKC) - Nik Muhammad Ridhwan, Nik Razali (2010)
This research is to design formulation of ostrich feed based on palm kernel cake. The palm kernel cake (PKC) are the by-product from the palm kernel production and the excess of these PKC are exported. However, the profit that we gain from the export is small. Thus, this research mainly about how to use this byproduct and use as feed input material in the ostrich feed production. So, the objectives is to study the right composition of palm kernel cake, justify the possibility of product using palm kernel cake as protein substitute in ostrich feed and lastly to determine the percentage of the raw material based on standard nutrient for the ostrich. Based on the given information, the composition of the feed was analyzed. There are three samples that has been formulated. These samples contain 25%, 30% and 35% of PKC. Then, these samples are compared with the standard nutrient required by the ostrich. The most suitable formulation is the usage of PKC of 30%. The process involve after the objective achieved is making it into a product. All the raw material will be grinding and then mixing. Then it will be analyze using the Near Infrared Analyzer (NIR) to make analyze that the right nutrient of the compound. Then, it will be mixed other substance as a binding to turn into pellet. The pellet that been produce will be compare with the standard ostrich feed. The product should be the same as the standard or it could be much better. Other raw materials are soybean, corn meal, fishmeal, limestone and oil palm fronds (OPF) were added to get the right nutrient composition. The cost of the manufacturing of ostrich can be reduced due to the usage of the PKC and the profit to the ostrich farming will be increase.